THE INFLUENCE OF ENTREPRENEURSHIP PERCEPTION ON ENTREPRENEURIAL INTENTION AMONG SCHOOL OF TOURISM STUDENT AT CIPUTRA UNIVERSITY, SURABAYA: ENTREPRENEURIAL ATTITUDE AS A MEDIATOR - Kezia Kezia Purwadi; Adrie Oktavio; Ellen Lawrencia Yahya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to examine the influence of entrepreneurial perceptions on the entrepreneurial intentions of school of tourism students which are mediated by entrepreneurial attitudes. The variables studied were Entrepreneurship Perceptions, Entrepreneurship Attitudes, and Entrepreneurial Intentions. Data collection was carried out by distributing questionnaires using purposive sampling to 88 School of Tourism students from three departments, namely Hotel and Tourism Business, Food Technology Program, and Culinary Business. The method used is descriptive quantitative with multiple regression analysis which tests four hypotheses with one independent variable; Perception of Entrepreneurship and two dependent variables; Entrepreneurial Attitude and Entrepreneurial Intention. The research results prove that Entrepreneurship Perception and Entrepreneurship Attitude have a significant influence on students' Entrepreneurial Intentions. Variable Entrepreneurship Perception has a positive but not significant effect on students' entrepreneurial intentions. The Entrepreneurial Attitude variable completely mediates the relationship between Entrepreneurial Perceptions and Entrepreneurial Intentions. Thus, it can be concluded that students state the importance of building an entrepreneurial attitude, because having an Entrepreneurial Perception is not enough to build students' entrepreneurial intentions. In further research will be possible to conduct research with a wider population of different objects